Determinan Penggunaan E-Money Pada Konsumen Pt. Indomarco Adi Prima Cabang Pekanbaru - Anisya Anisya; Adriyanti Agustina Putri; Rudi Syaf Putra (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to examine the effect of perceived usefulness, perceived ease of use, perceived risk, and perceived trust on the use of e-money among consumers at PT. Indomarco Adi Prima Pekanbaru Branch. In this study the method used for data collection was a questionnaire. The population in this study are Indomarco consumers who use e-money Indomarco Apps at PT. Indomarco Adi Prima Pekanbaru Branch. Sampling using random sampling method, with a total sample of 294 respondents. This research is a quantitative study with the data obtained processed using IBM Statistics SPSS 26. The results of the study indicate that the variables perceived benefits, perceived convenience, perceived risks, and perceived trust partially affect the variable use of e-money.